The Net has everything, but can it be trusted? - Abd Razak, Dzulkifli (2008)
“In the last election, we certainly lost the Internet war, the cyberwar.” Prime Minister Datuk Seri Abdullah Ahmad Badawi was quoted as saying this at the opening of Invest Malaysia 2008 last week, describing it as a painful lesson, and he reckoned that “it came at the right time”. Earlier, newlyappointed Information Minister Datuk Ahmad Shabery Cheek said the government would not control bloggers but would take into consideration their views as well. In fact, he recognised that the “alternative media, like bloggers, play a role in nation building”.